MULTIPLE ATTENUATION USING COMBINATION OF SURFACE RELATED MULTIPLE ELIMINATION AND RADON TRANSFORM METHODS OF SERAM SEA (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
Indonesia is a maritime country has a wealth of marine resources, in addition to abundant fishery products there are oil and gas in seabed rocks. Oil and gas exploration in Indonesia is still widely carried out today. One of the methods used in the search is seismic reflection method. The seismic reflection method utilizes sound wave generated by source. The waves will propagate into the earth's bedrock then are reflected back and received by the receiver. The 2D marine seismic data used in this study are raw data from acquisition in deepwater of Seram Sea, West Papua. Raw data from acquisition are still mixed with multiples due to different acoustic impedance of earth subsurface layers. This causes misinterpretation due to apparent reflector. Therefore, proper multiple attenuation methods are needed to minimize noise. This study applies combination of Surface Related Multiple Attenuation (SRME) and Radon transform to produce seismic cross section that are free of multiples. The obtained results shows the combination of SRME and Radon transform are effective to reduce long period multiples in near offset, middle offset and far offset. These combinations also relieve some insignificant primary reflectors due to mixed signal and multiple in the same moveout domain. The combination of these two methods is good for eliminating multiple types of water bottom multiple in deepwater seismic data, and improve the quality of the signal to noise ratio.